Penanganan Sengketa Ekonomi Syariah Perspektif Cita Hukum di Pengadilan Tinggi Agama Semarang - Jamaludin, Mohammad Jamaludin (AL-QARDH, 2020)
This article examines the handling of sharia economic disputes from the perspective of the ideals of law in the Religion High Court of Semarang, considering that up to now many decisions of the Religious High Court have been pursued at the cassation level (Supreme Court). The focus of this research study is to answer a number of issues, namely: how is the mechanism for handling sharia economic disputes in the Religion High Court of Semarang, what is the legal basis used by judges in the process of examining sharia economic disputes, and how the review of legal ideals towards handling sharia economic disputes in the Religion High Court of Semarang.